2017
DOI: 10.1021/acs.nanolett.7b00858
|View full text |Cite
|
Sign up to set email alerts
|

Mode Modification of Plasmonic Gap Resonances Induced by Strong Coupling with Molecular Excitons

Abstract: Plasmonic cavities can be used to control the atom-photon coupling process at the nanoscale, since they provide ultrahigh density of optical states in an exceptionally small mode volume. Here we demonstrate strong coupling between molecular excitons and plasmonic resonances (so-called plexcitonic coupling) in a film-coupled nanocube cavity, which can induce profound and significant spectral and spatial modifications to the plasmonic gap modes. Within the spectral span of a single gap mode in the nanotube-film … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 52 publications
(141 reference statements)
2
73
0
Order By: Relevance
“…An emerging field is to study the nanoscale light-matter interaction between plasmonic mode and few or even single quantum emitters (e.g., atoms, molecules or quantum dots, etc). For example, in the weak coupling regime LSPRs are widely used to enhance fluorescence [6][7][8] and Raman scattering [9][10][11] and to achieve unidirectional emission [12]; in the strong coupling regime the coherent hybridizations between plasmonic resonances and quantum emitters have also been investigated both theoretically [13][14][15][16][17][18] and experimentally [19][20][21][22][23][24][25].Two approaches have been taken to achieve singleemitter strong coupling -lowering the mode volumes and suppressing the dissipation. The former typically requires ultra-fine geometries with nanometer or even subnanometer precision [20,25], posing challenges on fabricating metallic structures and positioning individual quantum emitters.…”
mentioning
confidence: 99%
“…An emerging field is to study the nanoscale light-matter interaction between plasmonic mode and few or even single quantum emitters (e.g., atoms, molecules or quantum dots, etc). For example, in the weak coupling regime LSPRs are widely used to enhance fluorescence [6][7][8] and Raman scattering [9][10][11] and to achieve unidirectional emission [12]; in the strong coupling regime the coherent hybridizations between plasmonic resonances and quantum emitters have also been investigated both theoretically [13][14][15][16][17][18] and experimentally [19][20][21][22][23][24][25].Two approaches have been taken to achieve singleemitter strong coupling -lowering the mode volumes and suppressing the dissipation. The former typically requires ultra-fine geometries with nanometer or even subnanometer precision [20,25], posing challenges on fabricating metallic structures and positioning individual quantum emitters.…”
mentioning
confidence: 99%
“…The strong coupling regime generally requires cavities with high‐quality factors Qc=ωc/γc but it is also possible to exploit (SPP) thanks to their strongly localized evanescent electric field, which provides a high DOS in a small volume . This approach has made possible the coupling of excitons with nanoparticle SPP see also the previous section, as well as of molecular vibrations with a metallic film SPP . Although quantum strong coupling has a classical analogue, the purely quantum nature of the polariton states makes them useful for quantum information processing.…”
Section: Strong Coupling Applicationsmentioning
confidence: 99%
“…Similarly, a broadband GSP resonator was designed for PV applications using metal dewetting process which is a large scale compatible route . The effectiveness of this approach is not limited to semiconductors, but also thin organic coatings and dye molecules can also benefit from this strategy . Chikkaraddy et al demonstrated single‐molecule strong coupling at room temperature in plasmonic nanocavities gap .…”
Section: Light Trapping Schemesmentioning
confidence: 99%